2006
DOI: 10.1038/sj.bjc.6603156
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and differentiation of human breast cancer cells by the PAFR antagonist WEB-2086

Abstract: WEB-2086 -an antagonist of platelet-activating factor receptor (PAFR) with known anti-inflammatory, antiangiogenic and antileukaemic properties -also proved to inhibit the proliferation in human solid tumour cell lines of different histology, and with much higher efficacy than in normal fibroblasts. A detailed analysis of WEB-2086 anticancer activity was then performed focusing on breast adenocarcinoma MCF-7 and MDA-MB-231 cells. WEB-2086-treated cells, either expressing (MCF-7) or unexpressing (MDA-MB-231) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
24
0
2
Order By: Relevance
“…These findings were consistent with molecular biology results showing that WEB-2170 caused the downmodulation of several genes linked to cell proliferation and antiapoptotic pathways, while other genes promoting cell growth arrest, as well as the extrinsic and intrinsic apoptosis, were significantly upregulated. Apparently, the process was independent of p53 [26] and histone acetylation [13]. Moreover, we proved that WEB-2170 acts as an inverse agonist rather than an antagonist of PAF-r; this way, the drug induces the functional inactivation of PAF-r accompanied by a decrease in IP levels and this might be a critical metabolic event dictating the downstream inhibition of the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 82%
“…These findings were consistent with molecular biology results showing that WEB-2170 caused the downmodulation of several genes linked to cell proliferation and antiapoptotic pathways, while other genes promoting cell growth arrest, as well as the extrinsic and intrinsic apoptosis, were significantly upregulated. Apparently, the process was independent of p53 [26] and histone acetylation [13]. Moreover, we proved that WEB-2170 acts as an inverse agonist rather than an antagonist of PAF-r; this way, the drug induces the functional inactivation of PAF-r accompanied by a decrease in IP levels and this might be a critical metabolic event dictating the downstream inhibition of the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 82%
“…This effect was more pronounced in MDA-MB231 tumors as compared to tumors derived from non-metastatic cells [87]. Moreover, PAFR antagonist WEB-2086 induces growth inhibition and differentiation of human breast cancer cells [93], while the PAFR antagonist BN-50730 inhibited human prostatic carcinoma xenografts in nude mice [27]. Bocceline et al have found that PAF acts as a potent inducer of tumor cell motility in CHO cells in vitro [94].…”
Section: The Role Of Paf In Various Cancersmentioning
confidence: 96%
“…For example, the activation of PAFR can stimulate various kinases and the downstream signaling pathway to promote melanoma metastasis (7). Inhibition of PAFR activity by its specific inhibitor can effectively block the breast cancer cell growth and invasion in vitro (8). Disruption of the PAF/PAFR interaction or knockdown of the expression of PAFR can effectively block the invasion of ovarian tumor cells (9).…”
Section: Introductionmentioning
confidence: 99%